RETRACTED: Perkembangan Penulisan Ilmiah Berkaitan Sifat 20 Di Malaysia: Satu Sorotan - Abdullah, Mohd Azman; Engku Alwi, Engku Ahmad Zaki (Borneo International Journal of Islamic Studies, 2018)
RETRACTEDFollowing a rigorous, carefully concerns, and considered review of the article published in Borneo International Journal of Islamic Studies, Vol. 1(1), November 2018 to article entitled “Perkembangan Penulisan Ilmiah Berkaitan Sifat 20 Di Malaysia: Satu Sorotan ".This article contained plagiarism and it has been found to be in violation of the Borneo International Journal of Islamic Studies and it has been retracted.The document and its content has been removed from Borneo International Journal of Islamic Studies and reasonable effort should be made to remove all references to this article.